Upaya Pemerintahan Nagari dalam Penyelesaian Sengketa Tanah di Nagari Air Bangis Kabupaten Pasaman Barat - Putri, Annisa; Magriasti, Lince (Policy, Law and Political Research Center, 2023)
So this study aims to analyze and describe the efforts of the Nagari government in resolving land disputes in Nagari Air Bangis. The method used is qualitative-descriptive with informant retrieval techniques based on purposive sampling. The results showed that efforts have been made in resolving land disputes through five mechanisms, namely ADR (Alternative Dispute Resolution), Negotiation, Mediation, Arbitration and Neutral Fact-Finding. Efforts on the part of the Bangis Water Planters Solidarity began by conciliating the affected smallholders, the community and traditional leaders collecting historical evidence from the disputed customary land, the Nagari government facilitating meetings and expert teams, and WALHI accompanying the solidarity of bangis water planters and advocating. However, more authoritative actors, such as the Governor of West Sumatra and the Directorate General of the Ministry of Forestry of the Republic of Indonesia, have still not shown their role in resolving such disputes. The conclusion of the study shows that five efforts to resolve land disputes that occurred in Nagari Air Bangis have not been able to resolve the disputes that occurred so that they require more massive efforts from the government above Nagari.